Kedudukan Perempuan Migran Dalam Pandangan Islam & Kesetaraan Gender (Studi Pada Buruh Migran Perempuan di Desa Pengenjek) - Wadi, Hamzan; Heriyadi, Heriyadi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Migrant women are a hot issue for researchers and academics, because basically the ones who have the obligation to work, especially in positions that are very long distances and require a long time, are men or husbands. So that's the basic thing that causes being a migrant woman to cause a lot of debate within the family environment. The reason a wife or woman becomes a migrant worker or works abroad is because there has not been much change in the area of origin, especially to improve the family's economy. The problems studied are regarding the position of migrant women from an Islamic perspective and gender equality; study of female migrant workers in Pengenjek village. The researcher's target in this research is to find out the role of migrant women in Pengenjek village from an Islamic perspective. The data collection techniques that researchers used were observation and interviews. In data analysis, researchers use data reduction. In data reduction, researchers collect all data obtained in the field, both in the form of interview results, documentation and initial observation results. The results of this research are that Islamic migrant women are not wrong and violate household rules, because the basis for migrant women choosing to become migrant workers is very clear, such as helping the family economy and preparing for living costs and children's education. Apart from that, migrant women have received permission and blessing from their husband or family before they leave for the destination region and country. Meanwhile, according to gender equality, migrant women are already in the right choice. Because both husband and wife have the same right to work and develop their respective potential to become productive humans in the household. So that in developing this potential, husband and wife can do something that brings positive values to the family, but specifically for migrant women they still have to get permission from their husband.